Enforcing ship-based marine pollution for cleaner sea in the strait of Malacca. - Kasmin, Sutarji (Thai Society of Higher Eduction Institutes on Environment, 2010)
The Strait of Malacca is most susceptible to ship-based marine pollution such as oil and grease due to the heavy volume of shipping in the Strait. By nature, oil is toxic to marine life, especially the polycyclic aromatic hydrocarbons(PAHs), one of the main components in crude oil that is very difficult to clean up, and could remain for years in the sediment and marine environment. Marine species that are constantly exposed to PAHs can exhibit developmental problems and are more susceptible to diseases. The number of ships passing through the Strait in 2000 was 55,957 and increased to 62,621 ships 5 years later. In 2007, the traffic volume increased to 70,718 ships. During the five-year period from 2000 to 2005, there were 144 cases of oil spills into the sea. One hundred eight cases were due to illegal discharge of dirty oil. However, only 32 ships were charged and subsequently, 14 ships were found guilty. This paper analyses the challenges faced by the Malaysian maritime enforcement agencies in enforcing the Environmental Quality Act 1974 in the Strait of Malacca. Some of these challenges relate to the maritime enforcement agenciesû short-comings, nature of the Straitûs users and the legal processes to bring offenders to court. Based on the analyses, it was revealed that the responsible agencies are inadequately equipped and trained to deal with the illegal discharge of dirty oil into the sea. In order to overcome these weaknesses, several new initiatives are suggested.